Post-Marketing Health Technology Monitoring. The Analysis of an Experience from a Clinical Perspective - Ibargoyen-Roteta, Nora; Cabriada-Nuño, Jose Luis; Gutiérrez-Ibarluzea, Iñaki; Hernandez-Ramirez, Vicent; Clofent-Vilaplana, Juan; Domenech-Morral, Eugeni; Ginard-Vicens, Daniel; Oliva-Oliva, Gloria; Queiro-Verdes, Teresa (Frontiers in Pharmacology, 2011)
Introduction: A system for monitoring the use of aphaeresis in the treatment of Ulcerative Colitis (UC), named SiMAC, was designed in 2006 in the Basque Country. In the present study, the opinion of the clinicians who participated in SiMAC was evaluated, in order to identify the barriers and gather suggestions that could improve implementation of this kind of system. Methods: A mixed questionnaire was designed, in order to gather clinicians’ assessments of the SiMAC monitoring system. Results: The response rate was 73.9% (17/23). The data from 40.96% (159/388) of patients with UC treated with aphaeresis was recorded. The main reasons for not including the data from all treated patients were a lack of required data or not meeting the study inclusion criteria. Positive aspects of the SiMAC were identified, as the simplicity of data collection and its systematic, multi-centre approach. The negative aspects mentioned were the use of a local computer application and the lack of time for health professionals to enter data. Discussion: The use of monitoring systems helps to formalise the introduction of technologies of little-known effectiveness; involve clinicians and medical societies in coming to agreement and obtaining information about the safety, effectiveness or efficiency of new technologies; and provide relevant information to healthcare administrations for making decisions about the introduction of new technologies into healthcare practice. In order for a monitoring system to work, the process must be straightforward. A minimum set of key variables that are easy to collect must be selected, and an effort made to involve a range of stakeholders, especially institutions and scientific societies, to support the work group.